Alih Kode Dan Campur Kode Dalam Film Imperfect The Series 2 Yang Disutradarai Oleh Naya Anindita - Felicia Kurnia Apatama; Indra Perdana; Linggua Sanjaya Usop; Albertus Purwaka; Misnawati Misnawati (Universitas Palangka Raya, 2023)
The purpose of this study is to describe the forms of code switching and code mixing in Film Imperfect The Series 2 and to describe the causes of code switching and code mixing in Film Imperfect The Series 2. This research is a qualitative descriptive study. The data sources in this study were eight episodes of the film Imperfect The Series 2 . The form of data is in the form of words, sentences, and an event related to the form of code switching, and code mixing and the causes of its occurrence . The data in this study were collected by observing and note-taking techniques. Based on the results of the analysis, it can be concluded that overall in the eight episodes of the film Imperfect The Series 2 , there are 5 code switching data and 167 code mixing data. The forms of code switching found were internal code switching with 1 data and external code switching with 4 data. The forms of code mixing found were word forms with 119 data, phrase forms with 27 data and baster forms with 21 data. The cause of the occurrence of code switching found is that there are 2 data on the opponent's factor, 1 data on the presence of a third speaker and 2 data on the main factor/topic of conversation. The causes of code mixing were found to be the speaker factor with 51 data, the language factor with 112 data, and the desire to explain and interpret there were 4 data.